Immune response in breastmilk of Black women to SARS-CoV-2 infection and vaccination against COVID-19 - Smith, Maeve O.; Price, Jessica; Baker, Ryan; Neely, Halle; Alfandari, Dominique; Bugg, Kimarie; Sibeko, Lindiwe; Arcaro, Kathleen F. (Frontiers in Nutrition, 2026)
IntroductionIn the United States, Black lactating women are underrepresented in health-related studies. This underrepresentation is a concern when interpreting results from studies of the immune response to SARS-CoV-2 in breastmilk because we know that individuals vary greatly in their response to both infection and vaccination. Additionally, few studies of the immune response in human milk include analysis of mammary epithelium permeability, despite the knowledge that elevated permeability can alter constituents in milk. To address these gaps, we enrolled local Black breastfeeding mothers during a 3-day breastfeeding conference in New Orleans to assess the immune response in milk to infection or vaccination with SARS-CoV-2.Materials and methods3 weeks prior to the ROSE Black Breastfeeding & Birth Justice Summit of 25–27 August 2022, we advertised for “Black breastfeeding moms to participate in a health study of the special benefits of breastmilk during COVID-19.” Consented participants (n = 16) received kits with instructions to collect bilateral milk samples, dried blood spots (DBS), and saliva. Concentrations of anti-SARS-CoV-2 antibodies against both the Wuhan and Omicron variants were determined in milk, DBS, and saliva using the ELISA test. The concentration of a panel of cytokines was determined in milk, and the permeability of the mammary gland was assessed.ResultsAmong the 16 lactating women who provided samples, 8 had a positive COVID-19 test within the previous 19 months, and 12 had received an mRNA-based COVID-19 vaccine within the previous 16 months. Milk and maternal blood spots from all participants were positive for all anti-SARS-CoV-2 antibody classes tested, while only a subset of saliva samples were positive for all anti-SARS-CoV-2 antibody classes. A significant correlation was found between mammary epithelium permeability and concentrations of IL-1β, IL-6, and IL-8 cytokines.ConclusionResults from this small pilot study supported the need to include a diverse population in breastmilk studies, as the immune response in milk varied greatly among individuals. Future studies assessing the response to infections and vaccinations in lactating women should include analysis of milk from both breasts, as well as assessment of mammary epithelium permeability.